2016
DOI: 10.1159/000444495
|View full text |Cite
|
Sign up to set email alerts
|

Q787Q EGFR Polymorphism as a Prognostic Factor for Lung Squamous Cell Carcinoma

Abstract: Objective: EGFR genetic polymorphisms have been investigated for carcinogenesis in various tumors including lung cancer. We evaluated EGFR mutations in four exons, with an emphasis on the Q787Q EGFR polymorphism in non-small-cell lung cancer. Methods: To determine the presence of the Q787Q polymorphism in patients with lung cancer, we performed direct sequencing analyses of four exons for 83 squamous cell carcinomas and 80 adenocarcinomas untreated with EGFR tyrosine kinase inhibitors. Results: The Q787Q EGFR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…These authors also suggest a tendency toward better outcome in wild-type patients. Recently Koh et al, studying another Asiatic population, suggested, in agreement with Sasaki et al, that it could be an independent prognostic marker for low stage lung cancer patients [53]. In our study, we found no association of this marker with the most important mutations, p.L858R, and exon 19 deletions.…”
Section: Discussionsupporting
confidence: 87%
“…These authors also suggest a tendency toward better outcome in wild-type patients. Recently Koh et al, studying another Asiatic population, suggested, in agreement with Sasaki et al, that it could be an independent prognostic marker for low stage lung cancer patients [53]. In our study, we found no association of this marker with the most important mutations, p.L858R, and exon 19 deletions.…”
Section: Discussionsupporting
confidence: 87%
“…Another SNP (rs1050171; Q787Q) found to be associated with increased risk of AR but not with ESRD is located in exon 20 region of the EGFR gene. In the previous studies, the presence of this mutation was associated with worse prognosis in colorectal cancer and lung squamous cell carcinoma than that in the wild type [35,36]. As a synonymous variant, rs1050171 does not alter the amino acid sequence and structure of EGFR.…”
Section: Discussionmentioning
confidence: 80%
“…A study by Zhang et al (Zhang et al, 2006) also observed a higher incidence of p.Q787Q in lung cancer patients (64.8% in n 5 122) than in controls (51.7% in n 5 146), but did not analyze the impact on patient survival or therapeutic outcome. A recent study by Koh et al (2016) described considerably lower frequencies of p.Q787Q in NSCLC (overall 24% out of n 5 163) with 15.9% in ADC patients (n 5 80) and 24% in squamous cell carcinoma patients (n 5 83 (Koh et al, 2016)). A recent study by Koh et al (2016) described considerably lower frequencies of p.Q787Q in NSCLC (overall 24% out of n 5 163) with 15.9% in ADC patients (n 5 80) and 24% in squamous cell carcinoma patients (n 5 83 (Koh et al, 2016)).…”
Section: Discussionmentioning
confidence: 91%
“…The reported prevalence of the variant is in line with the data of our study (69.4% in 642 adenocarcinoma patients). A recent study by Koh et al (2016) described considerably lower frequencies of p.Q787Q in NSCLC (overall 24% out of n 5 163) with 15.9% in ADC patients (n 5 80) and 24% in squamous cell carcinoma patients (n 5 83 (Koh et al, 2016)). These frequencies are in good accordance with data on the prevalence of p.Q787Q in Korean individuals, which is reported to be considerably lower than in the European population (16.42% MAF in East Asians vs. 47.28% MAF in Europeans in ExAc).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation